(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the clinical and paraclinical features, alongside the treatment outcomes of hypophosphatemia among pediatric patients with severe dengue hemorrhagic fever (DHF) requiring invasive mechanical ventilation at Children’s Hospital 2. Methods: A retrospective case series study was implemented. The cohort included children diagnosed with severe DHF on mechanical ventilation who had serum phosphorus tests between January and December 2022. To mitigate confounding bias, two cases of early mortality upon admission (Glasgow Coma Scale = 3) were excluded. The study analyzed characteristics based on the severity of hypophosphatemia and compared outcomes between subgroups that received intravenous phosphorus supplementation and those that did not, specifically in severe cases. Results: Fifty-seven eligible pediatric patients were analyzed. The median age was 5.9 years (IQR 3-8), with males comprising 53%. The overall prevalence of hypophosphatemia was 84.2% (48/57), while severe hypophosphatemia accounted for 36.8% (21/57). At the lowest phosphorus level (nadir), the Glasgow score declined from 15 to 8, muscle strength weakened from 5 to 3.5, the PELOD-2 score climbed from 4.5 to 7, and the Vasoactive-Inotropic Score (VIS) surged from 0 to 10. The severe hypophosphatemia group (n=21) experienced a significantly longer duration of mechanical ventilation (median 7 vs. 4 days, p=0.005) and more days requiring vasoactive drugs (4 vs. 2 days, p=0.006) compared to the non-severe group (n=27). Notably, within the severe subgroup, patients receiving phosphorus therapy (n=13) demonstrated a reduced mortality rate and fewer ventilation days compared to untreated counterparts (n=8). Conclusions: Hypophosphatemia is highly prevalent among severe DHF children requiring mechanical ventilation and is associated with prolonged respiratory and hemodynamic support. Although preliminary retrospective data suggest favorable outcomes for the phosphorus-treated group, larger prospective trials are warranted to definitively confirm the survival benefits of this intervention.